ANALISIS KEUNTUNGAN USAHA GORENGAN â€œIBU NOUKEâ€ DI KELURAHAN BAHU KECAMATAN MALALAYANG KOTA MANADO - Hutri Di Tambajong; Mex Frans Lodwyk Sondakh; Melissa Lady Gisela Tarore (AGRI-SOSIOEKONOMI, 2020)
The purpose of this study is to analyze the benefits received by the fried home business industry in a single production process. This research was conducted in the Village Shoulder, Malalayang District, Manado City. This research was conducted for 3 months from October to December 2019. The data used in this study were primary and secondary data. Primary data was collected using direct interview techniques with business owners with the help of a list of questions prepared in advance. Data collected in this study were then analyzed using profit analysis using the formula for Revenue Cost Ratio (R / C) analysis. The results showed that the fried food business in the Village of Bahu, Bunaken District, Manado City was very profitable and got an R / C value of 1.35, which meant the industry was profitable and feasible to be developed. *eprm*